2016
DOI: 10.1016/j.jconrel.2016.01.042
|View full text |Cite
|
Sign up to set email alerts
|

A lipid nanoparticle for the efficient delivery of siRNA to dendritic cells

Abstract: Applying small interfering RNA (siRNA) to dendritic cell (DC) based therapy excess of 90%, with a median effective dose (ED50) of 1.5 nM, whereas the maximum gene silencing efficiency of Lipofectamine RNAi MAX was less than 60% and the EC50 was 25 nM. Furthermore, a suppressor of cytokine signaling 1, an immune suppressive molecule in DCs, silenced in the mouse DC by the YSK12-MEND showed a drastic enhancement in cytokine production, resulting in the significant suppression of tumor growth when it was applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
102
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(103 citation statements)
references
References 34 publications
(55 reference statements)
1
102
0
Order By: Relevance
“…The YSK12-MEND used in this study was composed of YSK12-C4, cholesterol, 1,2-dimyristoyl-sn-glycerol methoxyethyleneglycol 2000 ether (PEG-DMG) (85/15/1 mol ratio) and siRNA15. Although YSK12-C4 is an ionizable-cationic lipid, the pKa of the YSK12-MEND is 8.0.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The YSK12-MEND used in this study was composed of YSK12-C4, cholesterol, 1,2-dimyristoyl-sn-glycerol methoxyethyleneglycol 2000 ether (PEG-DMG) (85/15/1 mol ratio) and siRNA15. Although YSK12-C4 is an ionizable-cationic lipid, the pKa of the YSK12-MEND is 8.0.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study, we developed a multifunctional envelope-type nanodevice (MEND) for use as a non-viral delivery system14 and reported that a MEND containing YSK12-C4 lipid (YSK12-MEND) can be used to deliver siRNA to mouse DC15. YSK12-C4 is an ionizable-cationic lipid containing unsaturated carbon chains, which facilitate efficient endosomal escape.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The phagocytosis capability of macrophages from UCNPs treated mice was increased, demonstrating that NPs can stimulate innate immune response in vivo [87]. Recently, small interfering RNA (siRNA) modified NPs showed drastic gene silencing efficiency against the suppressor of cytokine signaling 1(SOCS1) gene in mouse DCs, leading to enhanced TNF-α and IL-6 production, and inhibited tumor growth in lymphoma bearing mice [88]. …”
Section: Therapeutic Immune Modulation By Engineered Nanoparticlesmentioning
confidence: 99%